2008
DOI: 10.1177/0193945908319249
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personalized Prenotification on Response Rates to an Electronic Survey

Abstract: The purpose of this post-hoc investigation was to determine the difference in response rates between respondents who received personalized prenotification prior to receiving an electronic survey and those who did not. An electronic survey was e-mailed to 236 program directors or other designated individuals from nurse practitioner (NP) programs around the United States. Seventy six percent of the NP program directors were personally contacted about the survey in advance, and 97.5% agreed to participate. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Hart, Brennan, Sym, and Larson (2009) reported little difference in participation based on pre-notification, so faculty received no advance notice before receiving the invitation for the study. Hart, Brennan, Sym, and Larson (2009) reported little difference in participation based on pre-notification, so faculty received no advance notice before receiving the invitation for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Hart, Brennan, Sym, and Larson (2009) reported little difference in participation based on pre-notification, so faculty received no advance notice before receiving the invitation for the study. Hart, Brennan, Sym, and Larson (2009) reported little difference in participation based on pre-notification, so faculty received no advance notice before receiving the invitation for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Kephart and Bressler (1958), in a study of nurses who had passed their Pennsylvania State Nursing Board examinations, found that a preliminary letter did not improve survey participation. However, more recent studies by Kulka et al (1981) and Hart et al (2009), found prenotification to be somewhat effective in improving nurse response.…”
Section: Impact Of Design-based Strategies On Nurse Responsementioning
confidence: 98%
“…There are also studies that combined some of the above-mentioned factors, to investigate whether it might result in higher response rates than using just one of these factors. However, results of such studies are inconclusive [11], [12], [13], [14], [15] and [16]. For instance, Slijkhuis et al [16] showed that using a prenotification and follow-up contact increased response rates compared with using only follow-up contact, whereas Hammink et al [13] combined prenotification and follow-up without any positive result.…”
Section: Introductionmentioning
confidence: 99%
“…Slijkhuis et al [16] also showed that sending a second paper questionnaire in combination with a prenotification did not influence response rates. Moreover, Hart et al [14] showed that personalized prenotification with an emailed survey did not have a significant positive effect on response rates. Beebe et al [11] investigated the impact of manipulating questionnaire length (two-vs. four page) and prenotification type (letter or postcard).…”
Section: Introductionmentioning
confidence: 99%